Perceptions about Indoor Residual Spraying For Malaria Prevention in the Savelugu-Nanton District, Northern Region, Ghana_2016 - Azure, P. N. (University of Ghana, 2016)
Background: Malaria is the number one cause of morbidity in Ghana, accounting for about 38% of all outpatient illnesses, 35% of all admissions and about 34% of all deaths in children. The World Health Organisation (WHO) recommends the spraying of at least 80% (ideally 100%) of houses, structures as well as units in target areas in any round of Indoor Residual Spraying. The Ministry of health intends to achieve at least 90% coverage in one third of the districts in Ghana by 2015. Indoor Residual Spraying (IRS) requires high spraying coverage and acceptance rate by households, to be effective. Local perceptions about IRS influence its acceptability, hence coverage. Objective: The objective of the study was to assess IRS related perceptions as a vector control strategy and its acceptability in the Savelugu-Nanton District. Methods: The study was a descriptive cross-sectional study that employed the mixed methods. A structured questionnaire was used in gathering quantitative data from 335 randomly selected household heads in a total of six communities. Qualitative data were collected through Focus Group Discussions. A total of four focus group discussions were held in four different communities. Analyses of quantitative data were done using excel 2010 and stata/SE 13 soft-ware. Tables and charts were generated and used to describe demographic data. Chi-square test was performed and used to describe the relationship between independent and dependent variables. Qualitative data were translated into English language and manually transcribed and coding of themes was done using Nvivo software. Thematic analysis was finally used to analyse qualitative data. Results: The majority (94.0%) of respondents indicated that malaria is caused by mosquito bites with only a few mentioning dirt and bites from bedbugs as the cause of malaria. About 99.4% of respondents have had their households sprayed at least once with the majority (86.5%) mentioning the killing of insects as a benefit of IRS. Only 29.0% mentioned reduction in malaria incidence as a benefit of the programme. Mentioning reduction in the incidence of malaria as a benefit was positively associated with being 50 years old or younger (OR= 2.8, 95% CI= 1.36-5.74and P>0.004). Among respondents and participants whose households have never been sprayed, refusals as well as absence of household heads during spraying were reasons that accounted for non-participation. Over 99.0% of respondents indicated that they will participate in future spraying exercises while 92.5% of them were considered knowledgeable about practices that can affect the functioning of the intervention. Varied types of malaria control strategies were reported and prominent among them was the use of bed net, 85.3%, (273). Conclusions: The study revealed that respondents as well as participants demonstrated a better understanding of the causes of malaria and the control strategies available. Indoor residual spraying was generally perceived to be beneficial. However associated benefits of IRS differed among respondents and study participants. Majority of respondents indicated that their households will continue to participate in spraying activities.
Thesis (M Phil) - University of Ghana 2016
Keywords: Malaria; Residual spraying